Vertical Characteristics of Raindrops Size Distribution over Sumatra Region from Global Precipitation Measurement Observation - Ravidho Ramadhan; . Marzuki; . Harmadi (Ital Publication, 2021)
The climatology of the vertical profile of raindrops size distribution (DSD) over Sumatra Region (10° S – 10° N, 90° E – 110° E) has been investigated using Global Precipitation Measurement (GPM) level 2 data from January 2015 to June 2018. DSD's vertical profile was observed through a vertical profile of corrected radar reflectivity (Ze) and two parameters of normalized gamma DSD, i.e., mass-weight mean diameter (Dm) and total drops concentration (Nw). Land-ocean contrast and rain type dependence of DSD over Sumatra were clearly observed. The values of Dm and Nw were larger in the land than in the ocean. Negative and positive gradients of Dm toward the surface were dominant during stratiform and convective rains, respectively, consistent with the Z gradient. Moreover, the negative gradient of stratiform rain in the ocean is larger than in land. Thus, the depletion of large drops is dominant over the ocean, which is due to the break-up process that can be observed from the increase of Nw. Raindrop growth of convective rains is more robust over the ocean than land that can be seen from a larger value of Dmgradient. The BB strength is slightly larger over land and coastal region than over the ocean, indicating that the riming process is more dominant over land and coastal regions than the ocean. Doi: 10.28991/esj-2021-01274 Full Text: PDF